Basic Short Service Technical Skills Based On Age Of Children In Pb Athletes. Asjad Badminton Club - Maruf; Y Touvan Juni Samodra; Rubiyatno; Rahmat Putra Perdana; Eka Supriatna (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
This study aims to determine the basic technical skills of short serve based on the age of the child. The method used in this research is a survey. The population in the study of male and female athletes who took part in the exercise was 40 people. The sample used is a population sample consisting of 40 athletes with details of 30 male and 10 female. Data collection tools used are tests and measurements of short service. The data analysis technique used quantitative descriptive statistics. The results of this study indicate that the short service ability based on the age of the sons and daughters has an average good category, with the following details: 8 years old 7 people (18%), 9 years old 5 people (13%), 10 years old there 13 people (33%), 11 years old 3 people (8%), 12 years old 6 people (15%), 13 year old 3 people (8%), 14 year old 2 people (5%) and 15 years old there is 1 person (3%).